2015
DOI: 10.12714/egejfas.2015.32.3.05
|View full text |Cite
|
Sign up to set email alerts
|

Effects of vitamin E, selenium and vitamin C on various biomarkers following oxidative stress caused by diazinon exposure in rainbow trout

Abstract: Biochemical parameters are appropriate biomarkers to assess the effects of pesticides on an aquatic ecosystem. Diazinon is an organophosphate pesticide whose metabolism in fish body produces reactive oxygen species that can cause oxidative stress. In this study, Oncorhynchus mykiss were allocated into four treatment groups (with three replicates): control; Diazinon; vitamin C + diazinon, and vitamin E,selenium + diazinon. Blood samples were obtained after two and four weeks and superoxide dismutase (SOD), cata… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 42 publications
0
2
0
Order By: Relevance
“…According to previous studies, the use of vitamin E and selenium can be enhance nonenzymatic antioxidant defense and adjust the levels of SOD and CAT to their normal values. Such an intervention can also increase TAC in fish ( Ali et al, 2015). Geetha et al (2010) reported that using chlorella extract supplement as an antioxidant compound in diet of Grey mullet (Mugil cephalus) in breeding environment could increase the total antioxidant level (Geetha et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…According to previous studies, the use of vitamin E and selenium can be enhance nonenzymatic antioxidant defense and adjust the levels of SOD and CAT to their normal values. Such an intervention can also increase TAC in fish ( Ali et al, 2015). Geetha et al (2010) reported that using chlorella extract supplement as an antioxidant compound in diet of Grey mullet (Mugil cephalus) in breeding environment could increase the total antioxidant level (Geetha et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…A determination of SOD activity was made according to the method used by Ali et al (2015). CAT activity was determined based on the methodology of Goth (1991).…”
Section: Methodsmentioning
confidence: 99%